Kenya : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper on Kenya reviews Kenya's external stability in a context where the exchange rate has strengthened and capital inflows are playing an increasingly important role. Kenya's external current account deficit has widened, reflecting strong import volumes as well as rising import prices, particularly for oil, but external debt as a percent of GDP has declined steadily. Underlying these developments have been a steady increase in capital inflows and a remarkable rebound of economic growth since 2003 after two decades of stagnation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet